The boundary value contact problem of electroelasticity for piecewise-homogeneous piezo-electric plate with elastic inclusion and cut. - Shavlakadze, Nugzar; Odishelidze, Nana; Criado-Aldeanueva, Francisco (SAGE, 2018)
In this paper a contact problem of the theory of electroelasticity for piecewise-homogeneous plate of piezo-electric material with infinite cut and elastic finite inclusion of variable bending rigidity is considered. By using methods of the theory of analytic function, the problem is reduced to a system of singular integro-differential equations with fixed singularity. Using an integral transformation, a Riemann problem is obtained, the solution of which is presented in explicit form.
El copyright pertenece a los autores.
Keywords: Problemas de contorno; Cálculo operacional; Materiales piezoeléctricos; Riemann problem; Asymptotic estimates; Contact problem; Elastic inclusion; Integral transformation; Integro-differential equations; Piezoelectric materials